2013
DOI: 10.1108/cb-03-2013-006
|View full text |Cite
|
Sign up to set email alerts
|

Comparing usage between selective and bundled e‐monograph purchases

Abstract: PurposeThe purpose of this paper is to present the results from a quantitative analysis comparing usage between collections of individually purchased e‐books and collections of e‐books purchased as part of large consortially negotiated bundles. The aim of this study is to determine if individually purchased e‐books have recorded a greater level of usage than e‐books purchased in large packages and, consequently, which of the two acquisition models is best suited for the library.Design/methodology/approachUsage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…This was achieved by dividing the number of viewings by the corresponding number of e-monographs (# viewings/# e-monographs) and will be reported as "viewings per e-monograph" ratios. Because Lamothe (2013aLamothe ( , 2013bLamothe ( , 2013cLamothe ( , 2010 has previously demonstrated that collection size can impact e-book usage rates, it is important to nullify this factor when comparing two or more collections of e-monographs of different size (Scanlan, 2008;Pendleton, 2005). Ratios also represent a relative value and should, by no means, ever be considered to be a measure of actual usage per e-monographs.…”
Section: Methodsmentioning
confidence: 97%
See 2 more Smart Citations
“…This was achieved by dividing the number of viewings by the corresponding number of e-monographs (# viewings/# e-monographs) and will be reported as "viewings per e-monograph" ratios. Because Lamothe (2013aLamothe ( , 2013bLamothe ( , 2013cLamothe ( , 2010 has previously demonstrated that collection size can impact e-book usage rates, it is important to nullify this factor when comparing two or more collections of e-monographs of different size (Scanlan, 2008;Pendleton, 2005). Ratios also represent a relative value and should, by no means, ever be considered to be a measure of actual usage per e-monographs.…”
Section: Methodsmentioning
confidence: 97%
“…Although recent studies have demonstrated the practicality of using e-book usage statistics to establish collection development best practices in academic libraries (Lamothe, 2013a;Romero, 2011;Bucknell, 2010;Grigson, 2009), they haven't addressed the effects that a Static Collection may have on its usage.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…45 In addition to a small number of locally purchased ebooks, Lamothe looked at use of three consortium-purchased bundles between 2007 and 2012 at Laurentian University. 46 There, 32 percent of 37,703 Springer titles in a consortium-purchased publisher package were used, 29 percent of a consortial bundle of 7,135 titles in NetLibrary and 6 percent of 7,800 titles in MyiLibrary. Slater examined use of 21,072 NetLibrary ebooks provided via consortium to users at Oakland University between 2005 and 2007.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Lamothe compared e-book usage from individual title purchases and packages in both NetLibrary and Ingram's MyiLibrary, along with Springer packages. 17 According to Lamothe, 66 percent of individually purchased books in NetLibrary were used compared to only 29 percent of the NetLibrary packages. With MyiLibrary, 72 percent of the individually purchases titles were used compared to 6 percent of package titles.…”
Section: Literature Reviewmentioning
confidence: 99%